THE INSTITUTIONAL EMPOWERMENT BUILDING OF THE THETHELAN (CROPS) FARMER ON REHABILITATION ZONE OF MERU BETIRI (TNMB) NATIONAL PARK IN EAST JAVA - Mulyono, Joko; Baratha, Lukman Wijaya; Mubarok, Ahmad Munif (Jurnal Partisipatoris, 2019)
The study entitled ? The institutional empowerment building of the crops farmer on rehabilitation zone of Meru Betiri national park in East Java? takes the fact that since the initialization of the Ecosystem Returns (PE) in 1999 in the rehabilitation zone until the year 2017, there is no optimum result of the program. Instead of getting greener, the zone becomes more dry, arid, and wither. The problem of the study is that what causes the PE program in rehabilitation zone ran less optimum? How to build the institutional empowerment of crops farmer? The purpose of this study is to identify factors that cause the less optimum of PE program at the rehabilitation zone and to formulate the model of optimum institutional empowerment of crops farmers. The primary data were through observation, interview, and Focus Group Discussion (FGD), while the secondary data were from a mixed document of Green?s ecological theory and Nort?s institution theory. Less optimum of PE program is due to the cultural switch from abstinence to anthropocentric, the scarcity of farming land, and market intervention. The model of institutional empowerment of crops farmer is the cooperation and synergy interaction among the actors.